Examining disparities in glycemic management: a comprehensive retrospective study on rural population - Andria Papazachariou; Onoufrios Malikides; Vironas Malikides; Nektaria Vasilaki; Maria Stamatelatou; Ioanna Papakitsou; Eleni Papadokostaki; Theodosios D. Filippatos (Discover Public Health)
Abstract Introduction Residing in rural or remote areas is often linked to compromised access to health services, directly affecting the feasibility of follow-up on patients with diabetes. There is a gap in the literature concerning the quality of diabetes care in rural areas and the relationship between glycemic control and distance to medical care. Methods An 8-month retrospective cohort study of factors affecting glycemic control among 932 individuals with diabetes, who sought medical care in a rural area. Demographics, comorbidities and laboratory measurements were retrieved through patient interviews, from the national electronic prescription system and hospital’s medical records. Distance in kilometers or in minutes from medical center was calculated using a geographic dataset. Results Participants (n = 632) resided within a half-hour proximity to reference center, demonstrated better glycemic control, with a mean HbA1c level of 7.20 ± 0.7%, as opposed to those (n = 300) who lived more than half-hour away, who exhibited a mean HbA1c level of 7.34 ± 0.8% (p = 0.016). HbA1c levels exhibit a significant correlation with both the time in minutes and the distance in kilometers from the rural area reference center. Multivariate linear regression analyses showed that distance in kilometers or in minutes is an independent factor influencing HbA1c levels. Conclusion The distance to medical services is an important factor of glycemic control in patients with diabetes, underlying the importance of improvements in the health system in rural areas.